Melihat Titik Temu Kemiskinan Dalam Pandangan al-Qur’an Dan Alkitab (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2022)
Poverty is a complex and multifaceted issue that extends beyond governmental concerns, encompassing the teachings of religious texts such as the Quran and the Bible. This article employs a qualitative approach and descriptive analysis to investigate how these religious texts approach poverty, and how they propose solutions to alleviate it. The study reveals that poverty is a societal malady that receives significant attention in both the Quran and the Bible. The Quran employs various terms, such as "miskin," "faqir," "da'if mustad'afun," "arazil or arzalun," "al-yatîm or al-yatâma," "al-sâil," and "al-mahrûm," to describe individuals who are economically challenged, while the Bible uses terms such as "ani," "dal," "ebyon," "penes" and "ptochos." It is noteworthy that the term "ptochos" in the Bible is analogous to "faqir" in the Quran, and similarly, the term "miskin" in the Quran is comparable to "penes" in the Bible. Moreover, the solutions to poverty proposed by both the Quran and the Bible are three-fold. First, a reconstruction of the theology of poverty is required. Second, collective awareness and efforts to eradicate poverty are necessary. Finally, a strong work ethic and spirit must be fostered to overcome poverty. In conclusion, poverty is a pressing issue that is addressed in both the Quran and the Bible, with proposed solutions emphasizing theological reconstruction, collective action, and a strong work ethic.
Keywords: Qur'an; Bible; Poverty